1997
DOI: 10.1093/emboj/16.23.7067
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular signal-dependent nuclear import of Stat1 is mediated by nuclear pore-targeting complex formation with NPI-1, but not Rch1

Abstract: In response to interferon-γ (IFN-γ), Stat1 is tyrosine phosphorylated and translocates to the nucleus where it activates transcription. In this study, we identified factors which mediate the nuclear import of Stat1. Tyrosine-phosphorylated Stat1 associated with the β subunit (a 97 kDa component) of the nuclear poretargeting complex via the NPI-1 family, but not the Rch1 family, of α subunit (a 58 kDa component) as a result of IFN-γ stimulation. Antibodies against NPI-1 or β subunit consistently inhibited the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
329
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(353 citation statements)
references
References 44 publications
17
329
1
3
Order By: Relevance
“…However, microinjection of this antibody not only inhibited the carrier-independent shuttling of unphosphorylated STAT1 in unstimulated cells, but also prevented the nuclear translocation of activated STAT1 in IFN-c-treated cells, which requires metabolic energy as well as the transport factors importin-a and importin-b (16,30,31). Accordingly, and contrary to the unphosphorylated STAT1 (Fig.…”
Section: Characterization Of a Stationary Stat1 Antibodymentioning
confidence: 86%
See 1 more Smart Citation
“…However, microinjection of this antibody not only inhibited the carrier-independent shuttling of unphosphorylated STAT1 in unstimulated cells, but also prevented the nuclear translocation of activated STAT1 in IFN-c-treated cells, which requires metabolic energy as well as the transport factors importin-a and importin-b (16,30,31). Accordingly, and contrary to the unphosphorylated STAT1 (Fig.…”
Section: Characterization Of a Stationary Stat1 Antibodymentioning
confidence: 86%
“…2A-2D) interferon-c expectedly had no influence on the distribution of either antibody. However, IFN-c treatment of cells triggers the association of both STAT1 and importin-b with the karyopherin importin-a, which affords their nuclear import via a GTPase-dependent mechanism (3,30,31). Surprisingly, while the translocating antibody accumulated in the nucleus, it nonetheless prevented the concurrent nuclear accumulation of STAT1 (Fig.…”
Section: Characterization Of a Translocating Importin-b Antibodymentioning
confidence: 96%
“…In this regard, it has been previously suggested that the nuclear import of activated Stat1 is mediated by NLS interaction with importin α5 [24,25]. Sekimoto et al showed that activated Stat1 associates with importin α5 and that its inhibition impairs nuclear translocation of Stat1 [24]. They also showed that dimerization is required for interaction with importin α5.…”
Section: Mechanisms Of Cytokine-induced Nuclear Import and Export Of mentioning
confidence: 99%
“…Both groups showed that this particular arginine/lysine-rich region mediates interaction with importin α, particularly importin α5 [22,23]. In this regard, it has been previously suggested that the nuclear import of activated Stat1 is mediated by NLS interaction with importin α5 [24,25]. Sekimoto et al showed that activated Stat1 associates with importin α5 and that its inhibition impairs nuclear translocation of Stat1 [24].…”
Section: Mechanisms Of Cytokine-induced Nuclear Import and Export Of mentioning
confidence: 99%
See 1 more Smart Citation